PELATIHAN BERKEBUN DENGAN MODEL KRPL (KAWASAN RUMAH PANGAN LESTARI) MELALUI PROGRAM BERSINAR (BERKEBUN DAN REHAT SEJENAK DENGAN AL-QUR’AN) DALAM UPAYA MEMBANGUN AGROWISATA - Faujan, Faujan; Az-Zahrah, Risya Jannah; Maulani, Restiana Adiati; Novitasari, Nastiti (Jurnal Pengabdian Masyarakat Indonesia, 2024)
Karikil Village is one of the many villages in the Mangkubumi Subdistrict with a highly strategic location, particularly in the fields of agriculture, plantations, and livestock. The natural wealth owned by the Karikil community also includes tourism or ecotourism within its area. Therefore, in this context, the improvement of the natural wealth's outcomes is a crucial part of the implementation of our Community Education Program themed Sustainable Food Area. The optimal utilization of backyard land with the Sustainable Food Area model as a support system is a crucial aspect in enhancing tourism, elaboration, and collaboration as the basis for improving Agrotourism in RW 1, Karikil Village, Mangkubumi Subdistrict, Tasikmalaya.